2011
DOI: 10.1149/1.3529938
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Oxalate Nanowires Grown on Electrochemically Deposited Ni Thin Film

Abstract: Nickel oxalate nanowires were produced by the reaction of nickel thin films electrochemically deposited on ITO glass in ethanolic oxalic acid. Their densities and lengths were strongly influenced by the thickness and roughness of the deposited nickel layers. The nickel layers became thicker with increasing deposition time, producing longer nanowires. Increasing roughness of the nickel layer led to shorter and denser nanowires. The total surface area of the nickel oxalate nanowires can be manipulated by the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…300–400 °C and atmospheric pressure 10 12 . Surface area of Ni metal can be further enlarged to Ni oxalate nanowires or nanosheets by oxalic acid etching 13 , while Ni metal phase can be resumed by annealing Ni oxalate under reducing or inert atmospheres 14 15 16 . In this work, NiO-decorated Ni nanowires (dia.…”
mentioning
confidence: 99%
“…300–400 °C and atmospheric pressure 10 12 . Surface area of Ni metal can be further enlarged to Ni oxalate nanowires or nanosheets by oxalic acid etching 13 , while Ni metal phase can be resumed by annealing Ni oxalate under reducing or inert atmospheres 14 15 16 . In this work, NiO-decorated Ni nanowires (dia.…”
mentioning
confidence: 99%
“…The theoretical initial discharge capacity of Cu-Sn-C thin film can be calculated considering the additional capacity coming from the presence of C (theoretical capacity: 372 mAh g −1 ), resulting in 618•95 mAh g −1 ((991 ×0•5924)+(372 ×0•0857) = 618•95 mAh g −1 ) as the first discharge capacity in total. This theoretical value is lower than the value shown in figure 5(c) (900 mAh g −1 ), which could be also explained, considering the SEI layer formation in the thin film surface (Jung and Lee 2011). The improved cycle retention and the high Columbic efficiency (>99%) detected after the first cycle can be related to the existence of additional C in the thin film, leading to a higher electrochemical performance of 450 mAh g −1 upto 80 cycles.…”
Section: Electrochemical Characterizationmentioning
confidence: 54%
“…These properties are expected to increase the conductivity and the mechanical tolerance of the thin film against the volumetric changes that occur during cycling (Kepler et al 1999;Belt et al 2003;Kawakami and Asao 2005;Mizutani and Inoue 2005;Zhang et al 2011). Cu-Sn phase diagram has various Cu x Sn y intermetallics:Cu 6 Sn 5 is * Author for correspondence (ozgulkeles@itu.edu.tr) remarkable due to its easy structural decomposition in a conductive Cu matrix (1) and (2) during the lithiation reaction (Kepler et al 1999;Jung and Lee 2011). In previous studies, it is shown that the anode made of Cu 6 Sn 5 particles has a longer cycle life compared to that of the pure Sn anode because during lithiation, lithium (Li) first reacts to form Li 2 Cu 6 Sn 5 (1), and then with further Li addition Li 2 Cu 6 Sn 5 decomposes into Li-Sn alloys (2) surrounded by Cu matrix (Besenhard et al 1986;Kepler et al 1999;Thackeray et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ni nanofoam with various diameters (100–1000 nm) can be synthesized by refluxing glycerol and Ni acetate (Ni(Ac) 2 ) . Ni can be further etched by oxalic acid into Ni oxalate nanowires and nanosheets to increase surface area, which can be further reduced back to Ni metal under inert or reducing atmosphere . In this work, Ni nanodendrite (ND, dia.…”
Section: Introductionmentioning
confidence: 99%